State Street: the Rise of a Distinct Personality in an Evolving Landscape - Unsworth, Ryan; Raasch, Sebastian; Graszer, Grace (My University, 2012)
State Street, a pedestrian mall located in Madison, Wisconsin, serves as a focal point in the city due to its central location and distinct geographic personality. While geographic personality is an exchange relationship that is unique to each individual, there are common characteristics of State Street that are experienced by all. Student surveys, observations and sketching depict an identity that can be expressed as: attractive, commercial, food-oriented, safe, social and walkable. Both repeat photography and Sanborn Fire Insurance Maps demonstrates the street's evolving physical landscape and how alterations in design have given rise to this personality.
Includes Bibliography, Charts, Appendix, Photographs and Maps.
Keywords: Pedestrian Mall; Madison, Wisconsin; State Street